The Expression and Therapeutic Potential of Checkpoint Kinase 2 in Laryngeal Squamous Cell Carcinoma - Tian Y; Wang Y; Xu S; Guan C; Zhang Q; Li W (Dove Medical Press, 2020)
Ying Tian,1 Yan Wang,1 Shan Xu,1 Chao Guan,1 Qingfu Zhang,2 Wei Li1 1Department of Otorhinolaryngology, The First Affiliated Hospital of China Medical University, Shenyang, People’s Republic of China; 2Department of Pathology, The First Affiliated Hospital and College of Basic Medical Sciences of China Medical University, Shenyang, People’s Republic of ChinaCorrespondence: Wei LiDepartment of Otorhinolaryngology, The First Affiliated Hospital of China Medical University, 155, Nanjing North Street, Heping District, Shenyang, Liaoning Province, People’s Republic of ChinaTel +86-13604077678Email wli@cmu.edu.cnIntroduction: Laryngeal squamous cell carcinoma (LSCC) is the most common histological subtype of laryngeal cancer. The involved molecular mechanisms and suitable therapeutic targets for LSCC still need to be further investigated. Checkpoint kinase 2 (CHK2) participates in several cellular physiology pathways and plays a role in tumor progression. However, the roles of CHK2 in LSCC remain unclear.Methods: mRNA expression data were obtained from The Cancer Genome Atlas (TCGA) database, and bioinformatic analysis was performed. Western blot and immunohistochemical analyses were conducted to detect protein expression. MTS assays were performed to examine cell growth of LSCC-derived cell lines.Results: In the present study, we found that both active form of CHK2 and total CHK2 protein expressions were up-regulated in LSCC tissues. Positive expression of CHK2 was closely associated with advanced clinical features and poor prognosis. Moreover, potential CHK2-involving bioprocesses and signaling pathways were analyzed. In addition, repressed proliferation of LSCC cells was induced by CHK2 inhibitor.Discussion: Taken together, our findings elucidated that CHK2 may act as an oncogenic factor in LSCC, suggesting a potential target for clinical treatment.Keywords: checkpoint kinase 2, laryngeal squamous cell carcinoma, BML-277, tumor growth